2009
DOI: 10.1080/07315724.2009.10719809
|View full text |Cite
|
Sign up to set email alerts
|

Milk Products, Insulin Resistance Syndrome and Type 2 Diabetes

Abstract: A growing body of evidence suggests an inverse relationship between calcium and vitamin D status and dairy food intake and the development of the insulin resistance syndrome (IRS) and type 2 diabetes mellitus (t2DM). Observational studies show a consistent inverse association between dairy intake and the prevalence of IRS and t2DM. In a systematic review of the observational evidence, the odds for developing the IRS was 0.71 (95% CI, 0,57-0.89) for the highest dairy intake (3-4 servings/d) vs. the lowest intak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
1
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(84 citation statements)
references
References 62 publications
5
72
1
6
Order By: Relevance
“…This fi nding is in agreement with the results from previous studies (101,102) performed on adults, which showed inverse associations between the intake of dairy products and type 2 diabetes. Overall, there is evidence of the benefi cial eff ect of daily intake of dairy products on glucose homeostasis, indicating a possible benefi cial eff ect of dairy consumption in the prevention of the development of type 2 diabetes (97).…”
Section: Dairy Products Can Reduce the Occurrence Of Type 2 Diabetessupporting
confidence: 83%
“…This fi nding is in agreement with the results from previous studies (101,102) performed on adults, which showed inverse associations between the intake of dairy products and type 2 diabetes. Overall, there is evidence of the benefi cial eff ect of daily intake of dairy products on glucose homeostasis, indicating a possible benefi cial eff ect of dairy consumption in the prevention of the development of type 2 diabetes (97).…”
Section: Dairy Products Can Reduce the Occurrence Of Type 2 Diabetessupporting
confidence: 83%
“…Clinical trials have shown that consumption of dairy foods has beneficial effects on levels of some cardiometabolic risk factors, including lipid profiles (42), hypertension (43,44), and insulin resistance (45). In addition, fermented dairy products and probiotic bacteria may have beneficial health effects on blood cholesterol, blood pressure, and immune function (46,47) and may provide prophylactic protection against heart disease (48), diabetes (49,50), and stroke (51).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, branched-chain amino acids (BCAAs), consisting of leucine, isoleucine and valine, are also reported to play an influential role in mediating insulin exocytosis , Gaudel et al 2013, while enhanced plasma levels correlated with increased IR in the presence of elevated lipids (Newgard 2012, Lu et al 2013. Interestingly, consumption of dairy products, which are a rich source of BCAAs, has been associated with improvements in both weight loss and T2DM management (Tremblay & Gilbert 2009, Jakubowicz & Froy 2013; consumption of whey protein hydrolysates have been suggested to improve fasting insulin levels, insulin release and glycaemic control in in vivo animal models and in obese and T2DM human subjects (Gaudel et al 2013, Jakubowicz & Froy 2013. However, the precise mechanism of these positive effects are not fully understood, but are believed to involve increased protein synthesis and possibly thermogenesis via activation of mammalian target of rapamycin (mTOR) signalling, increased anaplerosis and, in the case of leucine, enhanced allosteric activation of GDH that leads to increased TCA activity in the b-cell ( Fig.…”
Section: Amino Acid Metabolism and Insulin Secretionmentioning
confidence: 99%